Correlações genéticas de características de tamanho corporal e condição corporal com características de eficiência produtiva de fêmeas da raça Canchim - Baldi, Fernando [UNESP]; De Alencar, Mauricio Mello; De Freitas, Alfredo Ribeiro (FapUNIFESP (SciELO), 2008)
The objectives of this study were to obtain heritability estimates for number (NBZ10 and NBZT) and kilograms (QBD10 and QBDT) of calves weaned up to ten years of age and during herd life, kilograms of calves weaned per year in herd (QTPR) and their genetic correlations with culling age, ages at first, at second and at third calving, adjusted and unadjusted weights for condition score, body size indexes and condition score at first mating, at first calving and at mature age. Variance and covariance components were estimated by REML using univariate and bivariate models including the fixed effect of contemporary group and additive direct genetic and residual as random effects. Heritability estimates obtained from univariate analyses were 0.10 ± 0.05 (NBZT), 0.10 ± 0.03 (QBDT), 0.12 ± 0.05 (NBZ10), 0.13 ± 0.05 (QBD10) and 0.15 ± 0.05 (QTPR) and indicate low response by selection on these traits. Genetic correlation estimate suggest that selection for reducing age at first calving will not improve cow productivity. Selection for increasing mature weight will reduce kilograms of calves weaned per year in herd and the number of calves weaned up to ten years of age and during herd life. Selection on body size indexes and on cow weights adjusted for condition score may result in similar correlated responses in productive traits of cows, which would be higher than those from selection on unadjusted cow weights. © 2008 Sociedade Brasileira de Zootecnia.
Genetic correlations among cow body size, condition score and productive traits in Canchim cows
Keywords: Beef cattle; Cow body size; Genetic parameters; Kilograms of weaned calves; Number of weaned calves; Bos